Anti-inflammatory properties of hydroalcoholic extracts of Argentine Puna plants. (January 2015) - Torres Carro, Romina; Isla, María Inés; Ríos, José Luis; Giner, Rosa María; Alberto, María Rosa
Abstract: The aim of this study is to evaluate the activity of thirteen hydroalcoholic extracts obtained from aerial parts of plants from the Argentine Puna on pro-inflammatory enzymes and inflammatory mediators. Eleven extracts were non-cytotoxic on RAW 264.7. Data obtained suggest the capacity of these Argentine Puna plant extracts to inhibit the production of inflammatory mediators (nitric oxide and prostaglandin) at different levels. The plant extracts can affect enzyme expression and/or enzyme activity, and they can also act by NO scavenging. Each extract exerts its anti-inflammatory effect through different mechanisms. The inhibitory ability on pro-inflammatory enzymes by these hydroalcoholic extracts supports their potential use as sources of natural anti-inflammatory agents. Moreover, all extracts were non-toxic on Artemia salina toxicity test. The consumption of dietary supplements prepared with these plant species could be used to prevent the development of chronic inflammatory pathologies. Highlights: Argentine Puna plant extracts, are able to inhibit the production of inflammatory mediators at different levels. The natural compounds present in the extracts can also act by scavenging the nitric oxide produced by iNOS. Dietary supplements prepared with these plants could be used to prevent the development of chronic inflammatory pathologies.